The effect of tylosin exposure or exclusion on liver abscess prevalence, fecal pathogen populations, and the microflora of finished beef products from feedlot cattle - Weissend, Carla Jane, author; Martin, Jennifer, advisor; Belk, Keith, committee member; Bryant, Tony, committee member; Metcalf, Jessica, committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2018)
There is great pressure to reduce use of, and find alternatives to, antibiotics in animal production. More than 70% of feedlot cattle in 1000+ head lots are currently exposed to tylosin phosphate, a macrolide antibiotic used for the reduction and prevention of liver abscesses. As such, its potential removal from cattle feeding strategies could have a marked impact on both the economics of the beef industry and food safety. Additionally, little is known about the effect of tylosin exposure or exclusion on the microbiome of finished beef products. In light of these facts, a blinded, randomized, controlled field trial was conducted to evaluate the impact on the prevalence of liver abscesses and the characterization of the microbiome of feces, liver abscesses, carcasses, and finished beef products through 16S rRNA gene sequencing and shotgun sequencing from feedlot cattle with and without exposure to tylosin. Overall, liver abscess rates were lower among cattle exposed to tylosin. However, there were no differences among treatment groups for any of the sample types, suggesting that removal of tylosin from current feeding strategies will not upend the safety of the beef supply. The information gained in this study will provide valuable insight as the search for alternative feeding strategies to antibiotics continues.
Keywords: feedlot; liver abscess; AMR; microbiome; food safety